Information use and secondary school students: a model for understanding plagiarism - Kirsty Williamson; Joy McGregor (Information Research: An International Electronic Journal)
Introduction. The paper describes an interim model for understanding the influences on information use in relation to plagiarism, with a focus on secondary school students. Available literature mostly focuses on the tertiary level and on quantifying the extent of plagiarism, with limited availability of theory or empirical research focussing on information use, learning and plagiarism. Theoretical context: Possible theoretical bases for the model are considered, and the reasons for choosing Williamsons (2005) modified ecological model, as the basis, are outlined. Empirical Research: The data from a pilot study, using ethnographic techniques in a constructivist framework, contributed to the development of the interim model. The study was undertaken with Year 11 students in an Australian country high school. The data analysis from this study was influenced by constructivist grounded theory. Themes and categories were developed from this analysis. Model Development: The themes and categories, together with the gaps in understanding as revealed by the pilot research experience, were used to modify Williamsons ecological model to provide a diagrammatic representation suited to the topic of information use and plagiarism. The themes, encompassing a number of categories which might provide understanding about influences on information use in relation to plagiarism, are people, practices, attitudes and technology. Conclusion. Developing the model gave the researchers new insights at a crucial stage when they were about to embark on a major study, building on their pilot project. Although the target group for the research is secondary school students, the model is applicable to any group of information users.